Tachyon generalization for Lorentz transforms - Grushka, Ya. I. (Methods of Functional Analysis and Topology, 2013)
In the present paper we construct an expansion of the set of Lorentz transforms, which allows for the velocity of the reference frame to be greater than the speed of light. For maximum generality we investigate this tachyon expansion in the case of Minkowski space time over any real Hilbert space.